2018
DOI: 10.1016/j.envres.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Framework for the assessment of PEMS (Portable Emissions Measurement Systems) uncertainty

Abstract: European regulation 2016/427 (the first package of the so-called Real-Driving Emissions (RDE) regulation) introduced on-road testing with Portable Emissions Measurement Systems (PEMS) to complement the chassis dynamometer laboratory (Type I) test for the type approval of light-duty vehicles in the European Union since September 2017. The Not-To-Exceed (NTE) limit for a pollutant is the Type I test limit multiplied by a conformity factor that includes a margin for the additional measurement uncertainty of PEMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 11 publications
4
66
0
Order By: Relevance
“…A recent study at 20 mg/kWh levels found 10 mg/kWh measurement error (50%) [18]. In the EU, an uncertainty of approximately 45% at 80 mg/km levels was found (33 mg/km) assuming a drift of 5 ppm [16]. Thus, our older generation PEMS is between older PEMS assessments and the newer generation PEMS results (more details in Appendix B).…”
Section: Pems Assessmentmentioning
confidence: 65%
See 2 more Smart Citations
“…A recent study at 20 mg/kWh levels found 10 mg/kWh measurement error (50%) [18]. In the EU, an uncertainty of approximately 45% at 80 mg/km levels was found (33 mg/km) assuming a drift of 5 ppm [16]. Thus, our older generation PEMS is between older PEMS assessments and the newer generation PEMS results (more details in Appendix B).…”
Section: Pems Assessmentmentioning
confidence: 65%
“…This Appendix gives the PEMS uncertainty of heavy-duty vehicles based on the analysis that was conducted for light-duty vehicles [16]. The uncertainty values were taken from the regulation requirements regarding accuracy, linearity etc.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their simplified design and the additional uncertainties of tailpipe sampling, studies showed that they have differences of up to 50%-60% from the regulatory laboratory systems. This was based on testing campaigns with many systems and vehicles and inter-laboratory correlation exercises (e.g., [8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, uncertainty associated to the measurements can be propagated through the data used for emissions calculations. According to a study by the Joint Research Centre (JRC) of the EU [9] the main sources of uncertainty are the exhaust flow meter (EFM), the gas analyzers, and their drift. The extra PEMS measurement uncertainty compared to the well-established and more accurate legislated method (measurement of bags from a full dilution tunnel) is covered by a margin that determines the conformity factor.…”
Section: Introductionmentioning
confidence: 99%